Roteirização de veículos em centros urbanos: uma proposta de modelo matemático aplicado ao serviço de delivery com bicicletas - Vieira, Ricardo Luiz de Souza (2019)
The growth of cities has made urban freight transport a major challenge. It is possible to see that the growth rate of urban road infrastructure is lower than the growth of the number of vehicles and people, so that the negative impacts such as traffic congestion, pollution and accidents are increasingly impacting. One of the fastest growing transportation services in the cities is the delivery service, mainly food delivery, and it is very common to see motorcycles being used to make deliveries. An important concept that has emerged to address the interaction between people and the urban environment is City Logistics, which suggests the use of environmentally friendly urban transport. In this sense, the use of bicycles for the delivery service appears as an option to reduce the negative impacts. In this work, a mathematical model for the vehicle routing and programming was modified and applied to the delivery service considering the use of bicycles to make deliveries. The software Cplex was used to run 48 scenarios, where it was possible to demonstrate that the model can be solved in an optimal way for small instances, so that it can be used to optimize delivery routes with bikes.